2024
DOI: 10.1002/uog.27576
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of prenatal ultrasound in coarctation of aorta: systematic review and individual participant data meta‐analysis

C. Villalaín,
F. D'Antonio,
M. E. Flacco
et al.

Abstract: Objectiveto determine the diagnostic accuracy of prenatal ultrasound (US) in detecting coarctation of aorta (CoA).Methodsan individual participant data meta‐analysis was performed to report the strength of association and diagnostic accuracy of different US signs in detecting CoA prenatally. MEDLINE, Embase, and CINAHL were searched from January 2000 until November 2021. Individual participant‐level data was obtained by two leading teams. PRISMA‐IPD and PRISMA‐DTA guidelines were used for abstracting data and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Prediction of the presence or severity of aortic arch coarctation is challenging prenatally due to the presence of the ductus arteriosus, with its true severity often becoming evident only after the ductal constriction. Several studies have evaluated the utility of fetal echocardiographic findings in the prediction of postnatal coarctation, such as ventricular size discrepancy [19], aortic isthmus hypoplasia using gestational age-specific Z scores [20,21], increased distance between left common carotid to left subclavian branches, aortic arch curvature [22], and retrograde flow in the aortic isthmus [23]. However, none of these individual markers had high sensitivity and specificity for accurate coarctation prediction, and multi-parametric models integrating different fetal echocardiographic variables were proposed after a metanalysis study [24].…”
Section: Coarctation Of the Aortamentioning
confidence: 99%
See 1 more Smart Citation
“…Prediction of the presence or severity of aortic arch coarctation is challenging prenatally due to the presence of the ductus arteriosus, with its true severity often becoming evident only after the ductal constriction. Several studies have evaluated the utility of fetal echocardiographic findings in the prediction of postnatal coarctation, such as ventricular size discrepancy [19], aortic isthmus hypoplasia using gestational age-specific Z scores [20,21], increased distance between left common carotid to left subclavian branches, aortic arch curvature [22], and retrograde flow in the aortic isthmus [23]. However, none of these individual markers had high sensitivity and specificity for accurate coarctation prediction, and multi-parametric models integrating different fetal echocardiographic variables were proposed after a metanalysis study [24].…”
Section: Coarctation Of the Aortamentioning
confidence: 99%
“…However, none of these individual markers had high sensitivity and specificity for accurate coarctation prediction, and multi-parametric models integrating different fetal echocardiographic variables were proposed after a metanalysis study [24]. A more recent metanalysis study [21] again showed that although several prenatal ultrasound parameters can be associated with coarctation, their diagnostic accuracy is only moderate, even when parameters were used in combination. It has been reported that risk-based delivery and perinatal care planning in suspected coarctation can reduce unnecessary medical interventions [25].…”
Section: Coarctation Of the Aortamentioning
confidence: 99%
“…2,3,17,21 Positive predictive value is rising in combination with disproportion in three vessel view but is still not satisfying for many researchers. 15,18 Proper interpretation and diagnosis of CoA during fetal life, rise with experience of the sonographer. Competency in visualizing ductal and aortic arch in sagittal view is helpful with no doubt but is difficult to achieve and sometimes not possible because of the position of the fetus.…”
mentioning
confidence: 99%
“…The disproportion between aorta (A) and pulmonary artery (PA) in 3VV should be no more than 2 mm, or the index between them should be less than 1.5. [15][16][17][18] The differential may rise between second and third trimester, and it concerns 4CH and 3VV. 19 Disproportion, like other echocardiography findings in third trimester such as: trivial/mild tricuspid regurgitation or aneurysm of septum primum could be a result of the physiologic alteration.…”
mentioning
confidence: 99%